Dopant-free dithieno[3′, 2':3, 4;2″, 3'':5, 6]benzo[1, 2-d]imidazole-based hole-transporting materials for efficient perovskite solar cells. (April 2021) - Zeng, Qingliang; Li, Yang; Tang, Hao; Fu, Yajie; Liao, Chaoqiang; Wang, Lingyun; Xing, Guichuan; Cao, Derong
Abstract: Three dopant-free hole-transporting materials (HTMs) M1−3 containing dithieno[3′, 2':3, 4;2″, 3'':5, 6]benzo[1, 2-d]imidazole (DTBI) or phenanthro[9, 10-d]imidazole (PTI) were designed, synthesized and applied in perovskite solar cells (PSCs), where DTBI and PTI were first introduced as a core structure in the HTMs. Different steric groups (4-methoxybenzene and 4, 4′-dimethoxytriphenylamine) were introduced as the periphery groups connected at carbon-2 (C-2) position of imidazole moiety. Accordingly, the relationship between chemical structure and function was systematically investigated with respect to the fused cores and periphery groups, by the measurements of the energy levels, hole mobility, film-forming morphology, extraction and transfer of photo-generated holes, and photovoltaic performances. It was found that M1−2 with DTBI as a core structure exhibited suitable energy levels, higher hole mobility and uniform film-forming morphology, as well as efficient extraction and transfer of photo-generated holes at the perovskite/HTM interfaces. The PSCs using M2 as dopant-free HTM exhibited an impressive power conversion efficiency (PCE) of 16.9% with a negligible hysteresis, surpassing that of the doped spiro-OMeTAD-based standard device (16.4%) under the same testing conditions. Importantly, the unencapsulated PSCs based on dopant-free M2 presented much higher stability than that of doped spiro-OMeTAD. This work provides a promising strategy to construct dopant-free HTMs with both high efficiency and high stability by using DTBI as a core structure. Graphical abstract: Image 1 Highlights: HTM with dithieno[3′, 2':3, 4;2″, 3'':5, 6]benzo[1, 2-d]imidazole as core is designed. They are applied in PSCs as dopant-free hole-transporting materials (HTMs). They exhibit suitable energy levels and high hole mobility. They exhibit much higher stability over the doped spiro-OMeTAD in the ambient air.